Better load balancer design for signaling server in WebRTC communication - Kumar B. J, santhosh; Sankar, Nithya; V G, Karthika (International Journal of Engineering and Technology, 2018)
Most WebRTC applications can communicate through video and audio and other modes. WebRTC allows browser-to-browser multimedia imparting on the web. The proposed system emphasizes over the core architecture and allied technologies of WebRTC server accepting video input and producing output, multimedia transmission, peer-to-peer connection establishment and signaling mechanism. The system makes use of many components and focuses on designing a scalable load balancer architecture for the signaling servers. Currently there is a need of high quality and feasible solution that facilitate communication in the browser but WebRTC makes this possible and scalability feature is compared with open source (Licodeâ€™s WebRTC server).Â Â